Determination of distribution pattern, association, and interaction of plant species particularly the grassland in Baluran National Park, East Java - DJUFRI DJUFRI (Biodiversitas Journal of Biological Diversity, 2002)
The objectives of the research were : (1) to determine the distribution pattern, association, and interaction of plant species, (2) to determine the relationship between life form and the distribution pattern of species, and (3) to comparethe association chance of distribution patterns. Quadrate method was used in this project. Determination of speciesdistribution pattern was calculated using Poisson Distribution formula, and the determination of association was calculated using Contingency Table. The result indicated that: (1) The species richness were dominated by grasses, reaching 42.42%. Of the 33 observed species, 21 of them were in a clumped distribution, 7 species in a regular, and 5 species were at random pattern. (2) There are relationship between life form and the distribution of the plant species. The multi-plants tend to have a clumped distribution pattern, and single plant tend to have a regular or random distribution pattern. (3) The species of clumped distribution tend to have negative association to the species which of regular and random distribution pattern. However among the species which had the regular distribution pattern tend to have positive association. (4) The calculated results of the interaction more supported the individualistic concept of the plant association than community as an integrated unit.Â© 2002 Jurusan Biologi FMIPA UNS SurakartaKey words: distribution pattern, association, interaction, grassland, Baluran National Park